Transformational Principal Leadership in Enhancing Teacher Performance at SMP Negeri 1 Tanjung Raja - Yunie Aria Wati; Yasir Arafat; Reva Maria Valianti (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
This study aims to examine the role of school principal leadership in improving teacher performance at SMP Negeri 1 Tanjung Raja. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation, and documentation, with informants selected via purposive sampling and validated through method triangulation. The findings reveal that the principal consistently applies a democratic-transformational leadership style through three integrated strategies: open two-way communication, reflection-based post-supervision coaching, and dual motivation that combines public recognition with professional meaning reinforcement. This combination of strategies significantly enhanced teachers' commitment and instructional innovation. These findings serve as a practical reference for school principals and policymakers in designing teacher quality improvement programs, particularly in the context of implementing the Kurikulum Merdeka (Independent Curriculum).